15.9k views
0 votes
Which expression is equivalent to 4x + 2y + x - y after combining like terms?

Which expression is equivalent to 4x + 2y + x - y after combining like terms?-example-1
User Pandichef
by
5.3k points

1 Answer

4 votes

Hey there!


4x + 2y + x - y

= 4x + 2y + 1x - 1y


COMBINE the LIKE TERMS

= (4x - 1x) + (2y - 1y )

= 4x - 1x + 2y - 1y


= 3x + 1y


= 3x + y


Therefore, your answer is: 3x + y


Good luck on your assignment & enjoy your day!

~Amphitrite1040:)

User Jeanfrancois
by
5.8k points